KRAS mutations predict sensitivity to pemetrexed-based chemotherapy. (August 2013) - Levy, Benjamin; Drilon, Alexander; Chachoua, Abraham; Seetharamu, Nagashree; Richardson, Stacy; Lucido, David; Legasto, Alan; Grossbard, Michael; Becker, Daniel
SUMMARY Background: KRAS mutations, the most common oncogenic drivers in non-small-cell lung cancer, are found in at least a quarter of unselected cases. While data regarding the predictive nature of these aberrations has focused largely on targeted therapy, little is understood about the role of KRAS mutations in predicting sensitivity to cytotoxic chemotherapy.Aim: To evaluate clinical outcomes of patients with advanced adenocarcinoma of the lung harboring KRAS mutations treated with pemetrexed-based chemotherapy.Materials & methods: We performed a retrospective review of patients with advanced, KRAS -mutant and EGFR -wild-type ( KRAS + / EGFR - ) tumors receiving first-line chemotherapy containing pemetrexed and a platinum agent with or without bevacizumab. A second cohort of patients with KRAS - and EGFR -wild-type tumors ( KRAS - / EGFR - ) treated with a similar regimen was identified for comparison. Objective response rate (ORR) and progression-free survival (PFS) were compared between the cohorts.Results: Sixteen patients with KRAS + / EGFR - tumors and 19 with KRAS - / EGFR - tumors were identified. No significant differences in clinical characteristics between the two groups were noted, including age, gender, performance status, smoking or presence of brain metastases. Treatments did not differ statistically between cohorts in terms of cisplatin use, bevacizumab use, mean number of induction cycles or the use of either pemetrexed or pemetrexed–bevacizumab maintenance. ORR was better in the KRAS mutant tumors (56 vs 36%; p = 0.30), but did not reach statistical significance. PFS was longer in the KRAS + / EGFR - cohort (10.3 vs 5.7 months; p = 0.03).Conclusion: In this small retrospective series of patients treated with pemetrexed-containing chemotherapy, KRAS mutations were associated with a significantly longer PFS and a nonsignificant higher ORR.